The analytical basis for evaluating the innovative reflection engineering enterprises - O.Koleshchuk (Економіка, управління та адміністрування)
The article determines that in new economic conditions, in connection with the growth of innovativeness in management positions, the need for philosophical understanding of their foundations takes on a characteristic role, especially in strategic periods. It is established that in new turbulent economic conditions for the efficient operation of engineering enterprises and access to foreign markets, it is necessary to be actively engaged in innovative activities, which will increase their level in domestic and foreign markets. The author substantiates that the parameter that evaluates the potential capabilities for a machine-building enterprise, as well as determines the direction of innovation management on a strategic scale, is to assess the degree of innovation reflection, that is, to determine the level of readiness of the enterprise's line activity in the innovation process and on what scale. The article presents the innovative reflection as a multi-structural state determining the level of perception of the innovation process. It is determined that the resource component of innovative reflection is the basis for determining the degree of readiness of a machine-building enterprise for the implementation innovativeness and the formation managerial decisions, it includes the main components that have different functional significance. The author has formed the system of components for evaluating the innovative reflection of machine-building enterprises and their essence. It is determined that due to the spatial-dynamic assessment of the activity of machine-building enterprises in the areas (activity, adaptability, flexibility), in their components (investment, management, research, production, personnel, information, organizational, economic, financial), and according to their indications, it is possible to clearly determine the degree of innovative reflection engineering enterprises, and on their basis to form effective strategic management decisions as for the introduction of innovation to improve their competitiveness and expand into new markets. The evaluation of innovative reflection should be based on the analysis of internal environment of a machine-building enterprise, which allows one to assess the possibility and readiness of the enterprise to be innovative, analyze the trends in innovative development of the enterprise, to identify strengths and weaknesses, and formulate recommendations on the formation and implementation of strategic management of innovativeness for the machine-building enterprise.